2021
DOI: 10.3390/gels7020069
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization and Salt Effect on the Structure and Mechanical Properties of Polyacrylic Acid Gels under Equivolume Conditions

Abstract: The effects of neutralization and salt on the structure and mechanical properties of polyacrylic acid (PAA) gels under equivolume conditions were investigated by small-angle X-ray scattering (SAXS) measurements and tensile tests. We attained the equivolume condition by immersing a piece of PAA gel sample in an ion reservoir containing linear PAA, NaOH, and NaCl at prescribed concentrations (post-ion-tuning). The volume fraction of the linear polymer was set to be the same as that of the gel so as to satisfy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This behavior was due to the osmotic pressure caused by the difference in ion concentration in and outside the gel samples. 49 The percentage of swelling and deswelling in those solutions for the samples with different PPGDA concentrations is shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior was due to the osmotic pressure caused by the difference in ion concentration in and outside the gel samples. 49 The percentage of swelling and deswelling in those solutions for the samples with different PPGDA concentrations is shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that NaCl can reduce water intake. 49,51,52 The mechanical properties of the gels after swelling and deswelling were measured using tensile testing. The stress vs. strain data are plotted in Fig.…”
Section: Swelling and Deswelling Behaviormentioning
confidence: 99%